Foreign Aid and Income Inequality - Kim, Sewon (KDI School of Public Policy and Management, 2022)
This study contributes to the empirical understanding of aid effectiveness by examining the impact of foreign aid on income inequality in recipient countries. Impact of foreign aid on income inequality has been little studied despite the importance of the topic in terms of aid effectiveness, while among the existing literature, there is no consensus. This study utilizes both Pooled OLS and the Generalized Method of Moments (GMM) estimators for a panel of 156 countries covering the period 1997-2018. Data on inequality is extracted from the United Nation's World Income Inequality Database (WIID). The results indicate that foreign aid, controlling for other variables, is negatively correlated with income inequality at a statistically significant level, and the results are robust. Institutional variables, the level of democracy and control of corruption, are also incorporated to discern the relationship between foreign aid and governance. The results show that institutional variables have positive correlation with income inequality in an aid-receiving country. This implies that foreign aid may offset the equalizing effect of good governance, although overall, the equalizing effect of foreign aid on income inequality remains.
Keywords: Foreign Aid; Income Inequality; Aid Effectiveness; International Development; Governance; Panel Data; Generalized Method of Moments (GMM); World Income Inequality Database (WIID)